Serum 25‐hydroxy vitamin D concentrations are more deficient/insufficient in peritoneal dialysis than haemodialysis patients in a sunny climate. Issue 3 (11th April 2014) - Hanna, K.; Fassett, R. G.; Gill, E.; Healy, H.; Kimlin, M.; Ross, L.; Ash, S.
Abstract Background Research has identified associations between serum 25(OH)D and a range of clinical outcomes in chronic kidney disease and wider populations. The present study aimed to investigate vitamin D deficiency/insufficiency in dialysis patients and the relationship with vitamin D intake and sun exposure. Methods A cross‐sectional study was used. Participants included 30 peritoneal dialysis (PD) (43.3% male; 56.87 ± 16.16 years) and 26 haemodialysis (HD) (80.8% male; 63.58 ± 15.09 years) patients attending a department of renal medicine. Explanatory variables were usual vitamin D intake from diet/supplements (IU day−1) and sun exposure (min day−1). Vitamin D intake, sun exposure and ethnic background were assessed by questionnaire. Weight, malnutrition status and routine biochemistry were also assessed. Data were collected during usual department visits. The main outcome measure was serum 25(OH)D (nm). Results Prevalence of inadequate/insufficient vitamin D intake differed between dialysis modality, with 31% and 43% found to be insufficient (<50 nm) and 4% and 33% found to be deficient (<25 nm) in HD and PD patients, respectively (P < 0.001). In HD patients, there was a correlation between diet and supplemental vitamin D intake and 25(OH)D (ρ = 0.84, P < 0.001) and average sun exposure and 25(OH)D (ρ = 0.50, P < 0.02). There were no associations in PD patients. The results remained significant for vitamin D intake after multiple regression, adjusting for age, gender and sun exposure. Conclusions The results highlight a strong association between vitamin D intake and 25(OH)D in HD but not PD patients, with implications for replacement recommendations. The findings indicate that, even in a sunny climate, many dialysis patients are vitamin D deficient, highlighting the need for exploration of determinants and consequences.